Genital Self-Image and Aesthetic Genital Surgeries: Novel Perspectives Across the Cisgender and Transgender Spectrum. (5th July 2021) - Sharp, Gemma
Abstract: Genital-focused body image concerns or negative genital self-image are a common experience across the gender spectrum, including among cisgender and transgender populations. Such concerns can result in lower psychological and sexual well-being. In this article, it is proposed that the development of genital self-image concerns may be partly explained by the theoretical framework of cisgenderism. This theory proposes that there are only 2 genders—men and women—and these are dictated solely by the appearance of the genitals. Any deviation from these 2 categories can result in discrimination, which particularly impacts transgender individuals. An increasing number of cisgender and transgender people are seeking out aesthetic genital procedures to alleviate genital self-image concerns (and gender dysphoria in transgender populations). The growing body of research suggests that cisgender and transgender men and women are relatively satisfied with the results of their genital procedures. However, this research is limited by a lack of standardized and validated patient-reported measures to evaluate surgical outcomes. Furthermore, despite negative genital self-image being a key motivator for surgery, it is often not included as an outcome measure. In this article, recommendations are proposed for conducting higher-quality evaluation studies of aesthetic genital procedures in cisgender and transgender populations. Moreover, future research and clinical directions are suggested to assist transgender men and women who choose not to undergo genital gender-confirming surgery. The vast majority of transgender individuals do not have this surgery and so are in great need of support in managing their gender dysphoria and negative genital self-image.